A Base-Promoted One-Pot Asymmetric Friedel–Crafts Alkylation/Michael Addition of 4-Substituted Indoles - Connon, Robert; Carroll, Laura; Guiry, Patrick J. (Synthesis, 2020)
Herein, we report a base-promoted Zn(II)–bis(oxazoline)-catalyzed one-pot Friedel–Crafts alkylation/Michael addition of 3-(indol-4-yl)acrylonitrile derivatives with trans-β-nitrostyrenes to yield the tricyclic core of the ergoline skeleton in up to 71% yield and 85% ee. During the purification of 3-(indol-4-yl)acrylonitrile, the key substrate for catalytic studies, a novel trans-cis-trans-cyclobutane derivative, thought to be formed via a [2+2] light-promoted cycloaddition, was identified by X-ray crystallographic analysis. Finally, a novel class of 4-substituted bis(indole)methane derivatives were serendipitously prepared in excellent yield by reacting 4-substituted indole derivatives with 4-nitrobenzaldehyde. One bis(indole)methane was characterized by X-ray crystallographic analysis.
Keywords: enantioselective; oxazoline ligand; ergoline; indole; catalysis